The Role of Telemedicine in Expanding Pediatric Healthcare Access in Rural Areas - Obinna Nnamdi; Tope Adekunle Samuel (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Telemedicine has emerged as a vital tool in improving healthcare access for children in rural and underserved areas. This paper explores the growing role of telemedicine in providing consultations, diagnostics, and treatment plans remotely. By examining case studies from rural regions, the paper highlights how telehealth can bridge the gap in pediatric healthcare services, improving early diagnosis and treatment outcomes for children in these communities.